Effect of Epoxy Resin Emulsion on the Mechanical Properties of Oil Well Cement-Based Composites - Miao He; Jianjian Song; Mingbiao Xu; Lei He; Peng Xu (Advances in Civil Engineering)
Oil well cement is a brittle material, which can not ensure the long-term sealing integrity of oil and gas wells when used in cementing operations directly. As a kind of polymer emulsion material, epoxy resin emulsion has a bright future for improving the properties of the cement slurry. Epoxy resin emulsion was added to oil well cement and its workability and mechanical properties were studied, the stress-strain behavior of cement samples was evaluated, and the microstructure was observed by scanning electron microscope (SEM) and X-ray diffraction (XRD). The results show the epoxy resin emulsion used in oil well cement will affect the fluidity, but the rheological property of cement slurry with different content of resin meets the construction requirements. The resin reduces the water loss of cement paste and has no adverse effect on the thickening time. The compressive strength of cement stone decreases with the increase in resin content. When the content of resin is 6%, the flexural strength and impact strength of the cement sample are the largest, and 50.7% and 20.2% higher than that of the specimen without resin, respectively, after curing for 28 days. Further comparison shows that epoxy resin emulsion can improve the mechanical properties of oil well cement better than styrene-butadiene rubber latex. Meanwhile, the resin obviously improves the deformability and decreases the elastic modulus of cement stone. Compared with pure cement, resin cement slurry has no extra hydration products, but the formation of hydrated calcium silicate is inhibited. The microstructure shows that the resin forms a polymer film in the cement matrix and interweaves with cement hydration products, thus improving the flexibility of cement paste.